ICTV Virus Taxonomy Profile: Nanoviridae. (12th March 2021) - Thomas, John E.; Gronenborn, Bruno; Harding, Robert M.; Mandal, Bikash; Grigoras, Ioana; Randles, John W.; Sano, Yoshitaka; Timchenko, Tania; Vetten, H. Josef; Yeh, Hsin-Hung; Ziebell, Heiko; ,
Abstract : Nanoviridae is a family of plant viruses (nanovirids) whose members have small isometric virions and multipartite, circular, single-stranded (css) DNA genomes. Each of the six (genus Babuvirus ) or eight (genus Nanovirus ) genomic DNAs is 0.9–1.1 kb and is separately encapsidated. Many isolates are associated with satellite-like cssDNAs (alphasatellites) of 1.0–1.1 kb. Hosts are eudicots, predominantly legumes (genus Nanovirus ), and monocotyledons, predominantly in the order Zingiberales (genus Babuvirus ). Nanovirids require a virus-encoded helper factor for transmission by aphids in a circulative, non-propagative manner. This is a summary of the ICTV Report on the family Nanoviridae, which is available at ictv.global/report/nanoviridae .